Effects of Smartphone Activities on Postural Balance in Adolescents with Intellectual Disabilities - Ghada Jouira; Cristina Ioana Alexe; Julien Narcis Herlo; Cristina Elena Moraru; Mihaela Bogdan; Dan Iulian Alexe; Gabriel Mareș; Sonia Sahli (MDPI AG, 2023)
Considering the rising prevalence of smartphone usage among adolescents with intellectual disabilities and their frequent motor challenges, understanding its impact on their physical well-being is important. This study aims to investigate the impact of smartphone activities on postural balance in adolescents with intellectual disabilities. Two groups of adolescents participated in the study: an intellectual disability group (IDG) (n = 16) and atypical development group (TDG) (n = 12). Static postural balance, using a stabilometric platform on firm and foam surfaces, and dynamic balance, using the Timed Up-and-Go Test (TUGT), were performed under various conditions, such as playing a game, watching videos, video calls, and listening to music. The center of pressure (CoP) values significantly increased (p < 0.05) during all smartphone activities (except listening to music) compared to the control condition in both groups, with the IDG demonstrated a more pronounced increase (p < 0.05) during playing video games and video calls on the firm surface. TUGT scores significantly increased (p < 0.05) during smartphone activities, with greater changes observed in the IDG (p < 0.05), and significantly decreased (p < 0.01) during listening to music in both groups. Our study suggests that adolescents with intellectual disabilities need special tools and guidance to ensure their safety and well-being when using smartphones.